2018
DOI: 10.1007/s00774-018-0935-y
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92a-1-5p influences osteogenic differentiation of MC3T3-E1 cells by regulating β-catenin

Abstract: Osteoblastic differentiation is a complex process that is critical for proper bone formation. An increasing number of studies have suggested that microRNAs (miRNAs) are pivotal regulators in various physiological and pathological processes, including osteogenesis. Here, we discuss the influence of miRNA-92a-1-5p on osteogenic differentiation. We found that miR-92a-1-5p was obviously downregulated during osteogenic differentiation of MC3T3-E1 cells. Gain-of-function and loss-of-function experiments revealed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…MiR-92a-1-5p was a negative regulator of osteogenic differentiation. The expression of β-catenin was negatively regulated by miR-92a-1-5p, and the inhibition of miR-92a-1-5p on β-catenin was weakened by Wnt signal activator or GSK-3β knockout (Lin Z. et al, 2019). In addition, by regulating the expression of Wnt pathway related factors such as β -catenin, miR-26b-3p , miR-193a (Wang S. N. et al, 2018;, miR-4739 (Elsafadi et al, 2017), miR-150-3p (Wang N. et al, 2016), and miR-23a (Li et al, 2016) could also inhibit osteoblast differentiation but miR-101 (Wang H. et al, 2016) and miR-199b-5p (Zhao et al, 2016) could promote osteoblast differentiation.…”
Section: Wnt Pathwaymentioning
confidence: 98%
“…MiR-92a-1-5p was a negative regulator of osteogenic differentiation. The expression of β-catenin was negatively regulated by miR-92a-1-5p, and the inhibition of miR-92a-1-5p on β-catenin was weakened by Wnt signal activator or GSK-3β knockout (Lin Z. et al, 2019). In addition, by regulating the expression of Wnt pathway related factors such as β -catenin, miR-26b-3p , miR-193a (Wang S. N. et al, 2018;, miR-4739 (Elsafadi et al, 2017), miR-150-3p (Wang N. et al, 2016), and miR-23a (Li et al, 2016) could also inhibit osteoblast differentiation but miR-101 (Wang H. et al, 2016) and miR-199b-5p (Zhao et al, 2016) could promote osteoblast differentiation.…”
Section: Wnt Pathwaymentioning
confidence: 98%
“…17,18 miRNA-92a participates in the differentiation of osteoblast precursor cells into osteoblasts and can promote chondrogenesis. 19,28 In order to investigate the fracture healing and miRNA-92a-3p expression in patients with concomitant fractures and brain trauma, we collected samples from 30 patients (10 cases with completely healed fractures, 10 cases with isolated fractures, and 10 cases with concomitant fractures and brain trauma). The expression levels of miRNA-92a-3p in the plasma and callus were detected using RT-PCR.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental verification has shown that miR-92a-1-5p can negatively regulate β-catenin, a positive regulator of osteogenic differentiation. [ 35 ] There were also studies that the overexpression of miR-144-5p might reduce the viability of THP-1 macrophages by inhibiting the expression of Toll-like receptor 2 (TLR2) and inhibiting the activation of nuclear factor kappa-B (NK-κB) signaling and inhibit the expression of tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-8 in the cells. It was also proposed that miR-144-5p had the potential as a new therapeutic target for RA.…”
Section: Discussionmentioning
confidence: 99%